Utilization of Herbal Medicines as Alternative Hypertension Therapy: A Review of Effectiveness and Safety - Rifqi Ferry Balfas; Meilisa Carlen Mainassy; Desi Sri Rejeki; Lailiana Garna Nurhidayati (International Journal of Health Sciences, 2025)
Hypertension remains a leading cause of global morbidity and mortality, contributing to an increased risk of coronary heart disease, kidney failure, and stroke. Conventional hypertension treatment using synthetic drugs is effective in lowering blood pressure, but often causes side effects such as dizziness, dry cough, hypokalemia, and metabolic disorders that can reduce patient compliance with therapy. Therefore, people are starting to turn to complementary and alternative treatments based on herbal plants. This study aims to review the effectiveness and safety of using herbal medicines as an alternative therapy for hypertension based on the latest scientific evidence. The research method used is systematic review. literature review of 35 scientific articles from the database PubMed, ScienceDirect, and Garuda Dikti during the period 2015–2024. The results of the study showed that plants such as garlic (Allium sativum), celery (Apium graveolens), soursop leaves (Annona muricata), and pegagan (Centella asiatica) has the effect of lowering blood pressure through the mechanism of vasodilation, increasing the production of nitric oxide oxide , diuretic effects, and antioxidant activity. Although most studies show positive results, most of the trials are still preclinical and require confirmation through large-scale clinical trials. In conclusion, herbal medicines have the potential to be used as complementary therapies for hypertension with minimal side effects. However, their use must be monitored by medical personnel to avoid interactions with synthetic antihypertensive drugs.